2018
DOI: 10.1002/jbmr.3422
|View full text |Cite
|
Sign up to set email alerts
|

The Deletion of Hdac4 in Mouse Osteoblasts Influences Both Catabolic and Anabolic Effects in Bone

Abstract: Histone deacetylase 4 (Hdac4) is known to control chondrocyte hypertrophy and bone formation. We have previously shown that parathyroid hormone (PTH) regulates many aspects of Hdac4 function in osteoblastic cells in vitro; however, in vivo confirmation was previously precluded by preweaning lethality of the Hdac4-deficient mice. To analyze the function of Hdac4 in bone in mature animals, we generated mice with osteoblast lineage-specific knockout of Hdac4 (Hdac4 ) by crossing transgenic mice expressing Cre rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(108 reference statements)
0
16
0
Order By: Relevance
“…(19) One of the major anabolic effects of PTH in vivo and in vitro is inhibition of sclerostin (Sost) expression, a glycoprotein secreted by late osteoblasts and osteocytes. (19,48,49) The main function of sclerostin is to inhibit bone formation through inhibition of the canonical Wnt/β-catenin pathway. (50,51) There appeared to be a difference in the effect of PTH (1-34) and abaloparatide on Sost expression.…”
Section: Discussionmentioning
confidence: 99%
“…(19) One of the major anabolic effects of PTH in vivo and in vitro is inhibition of sclerostin (Sost) expression, a glycoprotein secreted by late osteoblasts and osteocytes. (19,48,49) The main function of sclerostin is to inhibit bone formation through inhibition of the canonical Wnt/β-catenin pathway. (50,51) There appeared to be a difference in the effect of PTH (1-34) and abaloparatide on Sost expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the importance of HDACs in pulpal mineralisation processes and odontoblast differentiation in vitro (Duncan et al, 2012;Duncan et al, 2013;Paino et al, 2014), but further work is required to understand HDACs role during tooth development in vivo. Deletion of HDAC-4 in mice inhibited bone resorption and reduced thickness and cortical bone mass (Nakatani et al, 2016), and had the additional effect of inhibiting MMP-13 and Sost/ sclerostin expression (Nakatani et al, 2018). Dentally, a mouse model of HDAC-4 KO demonstrated altered mineralisation in the roots of developing teeth (Ono et al, 2016) and the volume of enamel and dentine ( Figure 1A).…”
Section: Histone Acetylation Regulation Of Regenerative Mineralisatiomentioning
confidence: 99%
“…Class I HDACs demonstrate ubiquitous expression, while class II show tissuespecific expression and cellular localisations (Montgomery et al, 2007). The importance of class II HDAC expression in mineralising tissues has been demonstrated in bone (Ricarte et al, 2016) and teeth (Klinz et al, 2012), with the individual isoforms, -6 (Westendorf et al, 2002), -5, and -4 (Nakatani et al, 2018), highlighted as being important cellular mediators which regulate osteoblast differentiation. HDACs' roles in the regulation of mineralisation and developmental cellular processes (Gordon et al, 2015), also make them attractive therapeutic targets for pharmacological inhibition (Richon et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous HDACs are expressed and active in bone cells, their tight regulation is critical, as different HDACs exert variant effects on the different cell types (Table 3). For example, expression of HDACs 2, 4, 5, 6, and 7 is normally increased during osteogenesis [186,187,188,189,190,191], and deletion/inhibition of HDACs 2, 3, 4, 7, and 5/9 is associated with decreased BMD or altered bone structure [192,193,194,195,196,197,198,199,200,201,202,203,204]. A genome-wide association study even identified HDAC5 as one of 20 loci associated with osteoporosis [205], representing an independent risk factor for the development of HOD.…”
Section: Alterations In Transforming Growth Factor-β Superfamily Imentioning
confidence: 99%
“…Decreased levels of HDACs 3 and 4 are associated with increased bone catabolism, proposedly mediated via increased expression of FGF-21 and MMPs (e.g., MMP3, MMP10, and MMP13) [196,223,224,225]. Interaction with PTH, often increased during CLD, may alter HDAC4-dependent expression of these genes [225,226,227].…”
Section: Alterations In Transforming Growth Factor-β Superfamily Imentioning
confidence: 99%